Incidence and predictors of permanent pacemaker implantation following transcatheter aortic valve implantation: Analysis from the german transcatheter aortic valve interventions registry. Issue 4 (13th April 2013) - Ledwoch, Jakob; Franke, Jennifer; Gerckens, Ulrich; Kuck, Karl‐Heinz; Linke, Axel; Nickenig, Georg; Krülls‐Münch, Jürgen; Vöhringer, Matthias; Hambrecht, Rainer; Erbel, Raimund; Richardt, Gert; Horack, Martin; et al.
<x xml:space="preserve">Abstract</x> Objectives To determine predictors of permanent pacemaker (PPM) implantation up to 30 days after transcatheter aortic valve implantation (TAVI) in a prospective multicenter registry. Background Conduction disorders requiring PPM implantation are one of the most common complications seen after TAVI. Knowledge about possible predictors may help to decrease the rate of PPM implantations. Methods In total, 1347 consecutive patients who underwent TAVI in 22 centers were prospectively enrolled in the German transcatheter aortic valve interventions registry. Both Medtronic CoreValve™ and Edwards Sapien™ valves were implanted. Patients with preprocedurally implanted PPM or implantable cardioverter defibrillator were excluded from the analysis (n = 199). Regression analysis of baseline and procedure characteristics of the remaining 1, 147 patients was performed. Results Procedural success was achieved in 97.4% of the cases. The rate for PPM after TAVI was 33.7%. The absence of prior valve surgery, the use of Medtronic CoreValve™ prosthesis and the presence of a porcelain aorta were identified as independent predictors for PPM after TAVI. Mortality at 30 days did not differ between patients with or without PPM necessity (6.0% vs. 8.1%, respectively; HR 0.72; CI (0.45–1.16); P = 0.17). Conclusions PPM is a common postprocedure requirement after TAVI. The absence of prior valve surgery, the implantation of Medtronic CoreValve™ prosthesis, and the presence of a porcelain aorta were independently associated with PPM after TAVI. © 2013 Wiley Periodicals, Inc.